Cultivating Ecological Awareness Through the Integration of Eco-Linguistic Themes in English for Specific Purposes: A Case Study of Higher Schools of Technology - Fouad Boulaid; Handoko Handoko (Jurnal Gramatika, 2024)
: In pursuit of bolstering environmental consciousness, the integration of Eco-linguistic themes into English for Specific Purposes (ESP) classes emerges as a crucial pedagogical strategy. This study aims to explore the potential merits of embedding ESP within environmental education curricula, particularly in Higher Schools of Technology (HST), with a specific focus on augmenting students' comprehension of intricate ecological concepts and nurturing a new cadre of environmentally aware professionals. Given the imperative for effective interdisciplinary communication in tackling environmental issues, ESP, tailored to the language needs of environmental science, policy, and conservation, offers promise in furnishing students with the specialized language proficiency essential for precise communication within the field. The research endeavors to assess the extent to which ESP aids HST students in grasping complex ecological concepts that often necessitate technical terminology and nuanced language usage. Employing a mixed-methods approach, the study combines qualitative scrutiny of curriculum design and instructional methodologies with quantitative evaluation of students' language proficiency and comprehension of ecological principles. Educational institutions integrating ESP into their environmental education programs will be chosen as case studies. Interviews with educators and students, coupled with language assessment data, will furnish insights into the efficacy of ESP in enhancing language skills and fostering deeper comprehension of environmental content. Anticipated outcomes encompass a deeper understanding of ESP's impact on students' language proficiency and ecological acumen, as well as the identification of effective strategies for integrating ESP into environmental education. This research seeks to offer guidance to educators and curriculum developers endeavoring to bolster students' language skills and environmental literacy. Ultimately, by elucidating the advantages of incorporating ESP, this study contributes to ongoing discussions on pedagogical approaches that bridge the chasm between language education and environmental sciences. By highlighting the benefits of ESP integration, this research holds implications for shaping the curricula of environmental education programs and nurturing a cohort of professionals adept at effective communication, collaboration, and addressing the pressing environmental challenges of our era.